2014
DOI: 10.1002/jor.22693
|View full text |Cite
|
Sign up to set email alerts
|

Scapular dyskinesis is detrimental to shoulder tendon properties and joint mechanics in a rat model

Abstract: Shoulder tendon injuries are frequently seen in the presence of abnormal scapular motion, termed scapular dyskinesis. The cause and effect relationship between scapular dyskinesis and shoulder injury has not been directly defined. We developed and used an animal model to examine the initiation and progression of pathological changes in the rotator cuff and biceps tendon. Sixty male Sprague-Dawley rats were randomized into two groups: nerve transection (to induce scapular dyskinesis, SD) or sham nerve transecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…through improved scapular muscle balance (Merolla et al, 2010). The recent works of Reuther et al (2014Reuther et al ( , 2015 on an animal model also support a causative effect. Whatever the cause-effect relationship, it was shown that dyskinesis deeply affects functional scores (Harris et al, 2012), and it should always be evaluated and accounted for during rehabilitation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…through improved scapular muscle balance (Merolla et al, 2010). The recent works of Reuther et al (2014Reuther et al ( , 2015 on an animal model also support a causative effect. Whatever the cause-effect relationship, it was shown that dyskinesis deeply affects functional scores (Harris et al, 2012), and it should always be evaluated and accounted for during rehabilitation.…”
Section: Discussionmentioning
confidence: 80%
“…Its origin was related to pain, soft tissue stiffness, muscle recruitment pattern, force imbalance, muscle fatigue, thoracic postures, and it was reported as either a cause or an effect of shoulder pathologies (Ludewig and Reynolds, 2009;De Baets et al, 2013;Cools et al, 2013;Reuther et al, 2014). Despite the on-going debate, consensus exists that scapula dyskinesis is a potential impairment to shoulder function, that its assessment should be a routine part of the shoulder examination, and that addressing dyskinesis in the framework of a rehabilitation program improves outcomes (Kibler et al, 2013;McClure et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Seventy male Sprague Dawley rats (400-450 g) were randomized into 2 groups: nerve transection to create scapular dyskinesis (SD + Supra Repair group, n=35) or sham nerve transection (Sham + Supra Repair Group, n=35). For the nerve transection surgery, the spinal accessory and long thoracic nerves were visualized and transected as described by Reuther et al 36 For the sham nerve transection surgery, the nerves were visualized but were not transected. Following this procedure, all rats underwent unilateral detachment and repair of the supraspinatus tendon as described by Thomopoulos et al.…”
Section: Methodsmentioning
confidence: 99%
“…24, 27 Specifically, the abnormal loading environment in the presence of scapular dyskinesis alters the tendon composition and diminishes its mechanical properties. 36 It is likely that scapular dyskinesis is also detrimental to the supraspinatus tendon following surgical repair, compromising healing. Specifically, in the presence of scapular dyskinesis, the mechanical loading environment of the tendon is likely abnormal in both amount (i.e., overload) and type (i.e., compressive, shear) of loading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation